Anti‐β2M monoclonal antibodies kill myeloma cells via cell‐ and complement‐mediated cytotoxicity. Issue 5 (7th February 2014) - Zhang, Mingjun; Qian, Jianfei; Lan, Yongsheng; Lu, Yong; Li, Haiyan; Hong, Bangxing; Zheng, Yuhuan; He, Jin; Yang, Jing; Yi, Qing
<x xml:space="preserve">Abstract</x> Our previous studies showed that anti‐β2M monoclonal antibodies (mAbs) at high doses have direct apoptotic effects on myeloma cells, suggesting that anti‐β2M mAbs might be developed as a novel therapeutic agent. In this study, we investigated the ability of the mAbs at much lower concentrations to indirectly kill myeloma cells by utilizing immune effector cells or molecules. Our results showed that anti‐β2M mAbs effectively lysed MM cells via antibody‐dependent cell‐mediated cytotoxicity (ADCC) and complement‐dependent cytotoxicity (CDC), which were correlated with and dependent on the surface expression of β2M on MM cells. The presence of MM bone marrow stromal cells or addition of IL‐6 did not attenuate anti‐β2M mAb‐induced ADCC and CDC activities against MM cells. Furthermore, anti‐β2M mAbs only showed limited cytotoxicity toward normal B cells and nontumorous mesenchymal stem cells, indicating that the ADCC and CDC activities of the anti‐β2M mAbs were more prone to the tumor cells. Lenalidomide potentiated in vitro ADCC activity against MM cells and in vivo tumor inhibition capacity induced by the anti‐β2M mAbs by enhancing the activity of NK cells. These results support clinical development of anti‐β2M mAbs, both as a monotherapy and in combination with lenalidomide, to improve MM patient outcome.